2023
DOI: 10.1002/acn3.51763
|View full text |Cite
|
Sign up to set email alerts
|

Independent study demonstrates amyloid probability score accurately indicates amyloid pathology

Abstract: Background:The amyloid probability score (APS) is the model read-out of the analytically validated mass spectrometry-based PrecivityAD â blood test that incorporates the plasma Ab42/40 ratio, ApoE proteotype, and age to identify the likelihood of brain amyloid plaques among cognitively impaired individuals being evaluated for Alzheimer's disease. Purpose: This study aimed to provide additional independent evidence that the pre-established APS algorithm, along with its cutoff values, discriminates between amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…We used the same method for validating the PrecivityAD test, and that algorithm has since shown external validation in an orthogonal set of samples. 25 More studies are under way that seek to further demonstrate the robust clinical performance and generalizability of the APS2 model.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same method for validating the PrecivityAD test, and that algorithm has since shown external validation in an orthogonal set of samples. 25 More studies are under way that seek to further demonstrate the robust clinical performance and generalizability of the APS2 model.…”
Section: Discussionmentioning
confidence: 99%
“…A clinically and analytically validated mass spectrometry blood test and an algorithm combining Aβ42/40 ratio, ApoE proteotype and age (PrecivityAD blood test) variables yielding the APS has been previously described. 9 , 10 , 11 , 14 The main validation paper was focused on a cohort study that included analysis from two independent cross‐sectional cohort studies: the PARIS study, a prospective add‐on subset ( n = 249) to the Imaging Dementia–Evidence for Amyloid Scanning study (ClinicalTrials.gov Identifier: NCT02420756 ) as well as the cohort ( n = 437) of the MissionAD study (ClinicalTrials.gov Identifier: NCT02956486 ) who underwent amyloid PET testing. The reference standard used in this analysis was the presence or absence of brain amyloid on amyloid PET scan.…”
Section: Methodsmentioning
confidence: 99%
“…A more recently published analysis based on an independent cohort of participants from the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL) demonstrated that the PrecivityAD blood test with its validated, established cutoff values maintained high diagnostic accuracy for identifying the presence of absence of brain amyloid plaques. 11 In addition, two recent studies that evaluated the combination of plasma Aβ42/Aβ40 and APO Eε4 as well as the BBM combination plus age showed high correspondence with amyloid PET and provided Class II evidence that plasma Aβ42/Aβ40 levels accurately determine amyloid PET status. 12 , 13 …”
Section: Introductionmentioning
confidence: 98%
“…These tests showed the significant reliability of measuring brain amyloid plaques in individuals aged 55 and older with cognitive impairment. 8 9 His presentation also addressed the integration of blood biomarkers into routine clinical care, emphasizing diagnostic accuracy, clinical usefulness, and economic considerations in shaping the future role of blood biomarkers in cognitive care and management.…”
Section: Session 2: Blood-based Biomarkers For Ad In Clinical Practicementioning
confidence: 99%